Labor market regulations and the demand for labor in Brazil - Ricardo Paes de Barros; Carlos Henrique Corseuil; Gustavo Gonzaga (Institute for Applied Economic Research (ipea), 2015)
The main objective of this study is to evaluate the impact of the 1988 changes in labor market regulations on the level of employment and on the time required by firms to adjust their employment level to economic fluctuations. From the many aspects of labor market regulations, this study will concentrate on those that directly influence variable labor and dismissal costs. Evaluating the impact of changes in these costs on the level of employment and speed of adjustment will be based on estimates of structural dynamic models for labor demand at different points in time before and after the 1988 constitutional change. The empirical strategy will be to estimate such models from microlongitudinal monthly data for a sample of 5,000 on manufacturing establishments, which cover the period from January 1985 to December 1997. To try to isolate the effect of the constitutional change on the parameters of the demand function from the effect of the process of trade liberalization and of the series of stabilization plans that also occurred in the end of the 80's, we regress our monthly estimates of these parameters on a temporal indicator for the 1988 constitutional change, controlling for a variety of other macroeconomic indicators.
Keywords: 330